Outcome of a second hepatectomy in octogenarians with hepatocellular carcinoma recurrence: single centre's experience. Issue 10 (7th July 2019) - Ochiai, Toshiya; Inoue, Hiroyuki; Watanabe, Nobuyuki; Ito, Hiroshi; Toma, Atsushi; Morimura, Ryo; Ikoma, Hisashi; Otsuji, Eigo
Abstract : Background: Physicians rarely select surgery a second time as the treatment for octogenarians with hepatocellular carcinoma (HCC) recurrence. Methods: We encountered eight male and three female octogenarians underwent surgery a second time as the treatment for HCC recurrence (octo group). We studied these cases clinically and compared them with 25 younger people underwent surgery a second time (young group). All patients of octo group have resectable HCC according to the Japanese guideline, that is HCC patients with Child‐Pugh status A or B and who have solitary or only a few HCC nodules, in addition, no serious comorbidities, no serious dementia, a performance status of 0–1 and the will to receive hepatectomy. Results: The average maximum tumour size at the first hepatectomy was significantly larger than that at the second hepatectomy ( P < 0.05). The extent of the first hepatectomy was significantly greater than that of the second one ( P < 0.05). There were no mortalities at either hepatectomy. The morbidities of the first and the second hepatectomies were 9.1% and 18.2%, respectively. All complications were bile leakage. Furthermore, there were no significant differences in the clinical features, including the prognosis, between the octo and young groups. Conclusion: Selected octogenarians who received a second hepatectomy showed a relatively good post‐operative course after the first and second hepatectomies. Repeated hepatectomy for octogenarians seems to have same positive influence on the prognosis in comparison to the young group. But on the data analysed, we have not shown repeated hepatectomy is superior to non‐surgical treatments. Abstract : Repeated hepatectomy for octogenarians have same positive influence on the prognosis in comparison to the young group.